Teaching Based On A Creative Approach For Students Of Higher Educational Institutions As A Pedagogical Problem - Asadova, Sitora Sadullayevna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the development of students' creative approach skills as a pedagogical problem. In the modern education system, teachers are required to have the skills to effectively organize the lesson process, systematically organize educational materials, and apply modern approaches. The study reveals the components of design skills, the stages of its formation, and the pedagogical and psychological foundations of implementing this process in higher education institutions.